The recurrent postzygotic pathogenic variant p.Glu47Lys in RHOA causes a novel recognizable neuroectodermal phenotype. Issue 3 (24th December 2019) - Yigit, Gökhan; Saida, Ken; DeMarzo, Danielle; Miyake, Noriko; Fujita, Atsushi; Yang Tan, Tiong; White, Susan M.; Wadley, Alexandrea; Toliat, Mohammad R.; Motameny, Susanne; Franitza, Marek; Stutterd, Chloe A.; et al.
Abstract: RHOA is a member of the Rho family of GTPases that are involved in fundamental cellular processes including cell adhesion, migration, and proliferation. RHOA can stimulate the formation of stress fibers and focal adhesions and is a key regulator of actomyosin dynamics in various tissues. In a Genematcher‐facilitated collaboration, we were able to identify four unrelated individuals with a specific phenotype characterized by hypopigmented areas of the skin, dental anomalies, body asymmetry, and limb length discrepancy due to hemihypotrophy of one half of the body, as well as brain magnetic resonance imaging (MRI) anomalies. Using whole‐exome and ultra‐deep amplicon sequencing and comparing genomic data of affected and unaffected areas of the skin, we discovered that all four individuals carried the identical RHOA missense variant, c.139G>A; p.Glu47Lys, in a postzygotic state. Molecular modeling and in silico analysis of the affected p.Glu47Lys residue in RHOA indicated that this exchange is predicted to specifically alter the interaction of RHOA with its downstream effectors containing a PKN‐type binding domain and thereby disrupts its ability to activate signaling. Our findings indicate that the recurrent postzygotic RHOA missense variant p.Glu47Lys causes a specific mosaic disorder in humans.